Expression of the CDH1-associated form of the anaphase-promoting complex in postmitotic neurons - Gieffers, Christian (The National Academy of Sciences, 1999)
The anaphase-promoting complex/cyclosome (APC) is a tightly cell cycle-regulated ubiquitin-protein ligase that targets cyclin B and other destruction box-containing proteins for proteolysis at the end of mitosis and in G1. Recent work has shown that activation of the APC in mitosis depends on CDC20, whereas APC is maintained active in G1 via association with the CDC20-related protein CDH1. Here we show that the mitotic activator CDC20 is the only component of the APC ubiquitination pathway whose expression is restricted to proliferating cells, whereas the APC and CDH1 are also expressed in several mammalian tissues that predominantly contain differentiated cells, such as adult brain. Immunocytochemical analyses of cultured rat hippocampal neurons and of mouse and human brain sections indicate that the APC and CDH1 are ubiquitously expressed in the nuclei of postmitotic terminally differentiated neurons. The APC purified from brain contains all core subunits known from proliferating cells and is tightly associated with CDH1. Purified brain APC(CDH1) has a high cyclin B ubiquitination activity that depends less on the destruction box than on the activity of mitotic APC(CDC20). On the basis of these results, we propose that the functions of APC(CDH1) are not restricted to controlling cell-cycle progression but may include the ubiquitination of yet unidentified substrates in differentiated cells.